Inhibition Test of Hot Water Extract of Rhizophora apiculata Leaves Against Edwardsiella tarda Bacteria in-Vitro - Ronal Kurniawan; Sri Wahyuni; Fitrian Armando (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
One of the plants that have the potential as antibacterial ingredients is Rhizophora apiculata leaf because it contains secondary metabolites, such as tannins, saponins, flavonoids, steroids, and terpenoids. This study aims to find out the inhibition of hot water extract of R. apiculata leaves in inhibiting the growth of Edwardsiella tarda. The research method used is an experimental method which includes sample preparation, extraction, antibacterial activity test using the Kirby-Bauer disc method and applying a Completely Randomized Design (CRD). The doses used were 100% (10000 ppm), 90% (9000 ppm), 80% (8000 ppm), 70% (7000 ppm), 60% (6000 ppm), 50% (5000 ppm), 40% (4000 ppm), 30% (3000 ppm), 20% (2000 ppm), 10% (1000 ppm) and control (Oxytetracycline). The results showed that the hot water extract of R. apiculata leaves at a dose of 1000-10000 ppm gave various inhibitory diameters ranging from 6.25-10.08 mm and the clear zone formed was classified as medium